Skin‐to‐skin contact during eye examination did not reduce pain compared to standard care with parental support in preterm infants. (18th January 2019) - Kristoffersen, Laila; Støen, Ragnhild; Bergseng, Håkon; Follestad, Turid; Theodorsson, Elvar; Vederhus, Bente; Adde, Lars; Austeng, Dordi
Abstract: Aim: We compared the pain relieving effect of skin‐to‐skin contact versus standard care in the incubator during screening for retinopathy of prematurity. Methods: This randomised crossover study included 35 preterm infants of less than 32 weeks of gestational age admitted to St Olavs University Hospital, Trondheim, Norway, between January 2014 and June 2016. Randomisation was for skin‐to‐skin with one of the parents or standard care with supportive positioning by parents for the first of two consecutive eye examinations. The pain score was measured twice using the Premature Infant Pain Profile (PIPP) during and after the eye examination. The infants' movement activity was video recorded after the examination. Results: There was no difference in mean pain scores with skin‐to‐skin contact versus standard care during (10.2 vs. 10.3, p = 0.91) or after (7.0 vs. 6.8, p = 0.76) the procedure. Independent of the randomisation group, PIPP scores were lower than previous comparable studies have found. Bouts of movement activity were also the same whether the examination was conducted in skin‐to‐skin position or in the incubator (p = 0.91). Conclusion: Skin‐to‐skin contact during the eye examination did not provide additional pain relief compared to standard care where the parents were already a part of the multidimensional approach.